Pengaruh Academic Supervision Of School Heads Dan Interpersonal Communication Terhadap Teacher Performance Sekolah Dasar Negeri Jakarta Selatan - Ratih Kusuma Wardani; Heru Santosa; Desi Rahmawati (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The purpose of this study is to determine whether there is a direct positive effect from Principal’s academic supervision and interpersonal communication on teacher's performance. Total of 59 teachers were chosen as research samples to obtain data and analyzed using quantitative methods of path analysis. The results showed that there is a direct positive effect (1) academic supervision on teacher performance, (2) interpersonal communication on teacher's performance, (3) academic supervision on interpersonal communication is positive direct effect.